Topics in Dynamics : I: Flows - Nelson, Edward, 1932- (Book collections on Project MUSE., 1969)
Kinematical problems of both classical and quantum mechanics are considered in these lecture notes ranging from differential calculus to the application of one of Chernoff's theorems. Originally published in 1970. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase.